Comparative studies of RSM Box-Behnken and ANN-Anfis fuzzy statistical analysis for seawater biodegradability using TiO2 photocatalyst. (February 2023) - Mohammed, Nayeemuddin; Palaniandy, Puganeshwary; Shaik, Feroz; Mewada, Hiren; Balakrishnan, Deepanraj
Abstract: In this approach, a batch reactor was employed to study the degradation of pollutants under natural sunlight using TiO2 as a photocatalyst. The effects of photocatalyst dosage, reaction time and pH were investigated by evaluating the percentage removal efficiencies of total organic carbon (TOC), chemical oxygen demand (COD), biological oxygen demand (BOD) and biodegradability (BOD/COD). Design Expert-Response Surface Methodology Box Behnken Design (BBD) and MATLAB Artificial Neural Network – Adaptive Neuro Fuzzy Inference system (ANN-ANFIS) methods were employed to perform the statistical modelling. The experimental values of maximum percentage removal efficiencies were found to be TOC = 82.4, COD = 85.9, BOD = 30.9% and biodegradability was 0.070. According to RSM-BBD and ANFIS analysis, the maximum percentage removal efficiencies were found to be TOC = 90.3, 82.4; COD = 85.4, 85.9; BOD = 28.9, 30.9% and the biodegradability = 0.074, 0.080 respectively at the pH 7.5, reaction time 300 min and photocatalyst dosage of 4 g L −1 . The study reveals both models found to be well predicted as compared with experimental values. The values of R 2 for RSM-BBD (0.920) and for ANFIS (0.990) models were almost close to 1. The ANFIS model was found to be marginally better than that of RSM-BBD. Graphical abstract: Image 1 Highlights: Statistical analysis for the removal of pollutants in seawater using TiO2 under natural light was investigated. RSM-BBM and ANN-ANFIS models were applied for the optimization of process parameters. Experimental results showed substantial removal of pollutants from the seawater. The % removal efficiencies of various parameters were estimated. ANN-ANFIS modelling predicted better values as compared to RSM modelling.